Narkotisko vielu neatļautas aprites izmeklēšanas mūsdienu prakse Latvijā - Felšane, Laura (Latvijas Universitāte, 2012)
Diplomdarbs "Narkotisko vielu neatļautas aprites izmeklēšanas mūsdienu prakse Latvijā" ir izstrādāts ar mēŗķi atspoguļot izmeklēšanas procesa gaitu lietās par narkotisko vielu neatļautu apriti un vērst uzmanību uz tiesiskas dabas problēmām, ar kurām jāsaskaras Valsts policijas amatpersonām iecirkņa līmenī izmeklējot narkotisko vielu neatļautas aprites gadījumus, kā arī sniegt priekšlikumus to risināšanai. Darbs sastāv no trīs nodaļām. Pirmā nodaļa sniedz narkotisko vielu neatļautas aprites vispārēju raksturojumu. Otrā nodaļā tiek veikta narkotisko vielu neatļautas aprites lietās pierādāmo apstākļu analīze un sniegts šo noziedzīgo nodarījumu kriminālistiskais raksturojums.Trešajā nodaļā tiek skatītas raksturīgākās izmeklēšanas darbības un to veikšanas īpatnības narkotisko vielu neatļautas aprites lietās.

Diploma thesis of Laura Felsane, student of the University of Latvia „Contemporary practice of investigation of illegal drug turnover in Latvia” is a result of the consolidation of her own investigative experience, and creative manipulation of materials obtained during interviews with colleagues and explore scientific and practical literature. The work consists of three chapters, which covers issues such as: 1) the general characteristics of illegal drug turnover, 2) forensic characterization of the investigated types of crimes, and 3) the tactics of individual actions during investigation. The study provides a historical overview of the problem of drug-related crime, combat, characterized by certain types of drugs and analysis of the Latvian law stipulating responsibility for the person involved in drug trafficking. The author describes the most common ways to commit crimes and cover-ups, typical traces of the criminal drug activity and ways of fixing these traces. Based on real criminal cases the characteristic of the perpetrators. The author analyzes the tactics of investigative actions such as detention of suspects, personal searches and searches of various storage, inspection and examination, questioning suspects and witnesses, confrontation and examination appointment.
Contemporary practice of investigation of the illegal drug turnover in Latvia
Keywords: Juridiskā zinātne